Characteristics of water-soluble organic carbon associated with aerosol particles in the eastern United States - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M. (Atmospheric Environment, 2012)
Desorption kinetics and sources (fossil vs. contemporary) of the water soluble organic carbon (WSOC) component of aerosol particles were examined at two sites on the east coast of the United States. Experiments revealed that WSOC is released either rapidly as one homogeneous pool or via biphasic kinetics with one rapidly and one slowly desorbing pool. The majority (>85%) of WSOC was desorbed within the first 15 min of immersion in water, suggesting that this material can be rapidly incorporated into rainwater pre-depositionally or surface waters post-depositionally and transported through watersheds. Radiocarbon (14C) measurements showed that on average 12 ± 4% and 14 ± 2% of WSOC from sites in New York and Virginia, respectively, was derived from fossil sources. By contrast, mass balance calculations revealed water-insoluble organic carbon to have significantly greater fossil contributions. These findings suggest that contemporary biogenic aerosol OC is preferentially incorporated into the aqueous phase and may be transported relatively rapidly through watersheds and aquatic systems. In contrast, the more highly aged and fossil aerosol component remains in particulate form and is more likely to be retained on particles or in soils or aquatic sediments.
id: 2153